The Students’ Perception of The Impacts of Classroom Physical Environment towards Students’ English Learning Motivation - Orun , Putri Anugraheli Ramba (Yayasan Nurul Iman Muara Gading Mas, 2024)
The primary objective of this study is to examine the correlation between students’ perceptions of the Classroom Physical Environment and their motivation to learn English at SMP Negeri 1 Biak Timur. A quantitative methodology was employed for both data collection and analysis. The research utilized a questionnaire to gauge students’ perceptions of the physical classroom environment, alongside a motivation scale tailored for English learning. The research sample consisted of 30 randomly selected students. Results from the data analysis, conducted using the chi-square statistical test, revealed a calculated chi-square value of 17.0417, surpassing the critical value of 9.488 at a significance level of 0.05, with degrees of freedom of (df=4). This indicates a significant association between students’ perceptions of the Classroom Physical Environment and their motivation to learn English. The implications of these findings for instructional methodologies are discussed comprehensively, along with suggestions for future research endeavors.